A4NH study challenged thinking around the global focus on lowering the prevalence of stunting, successfully encouraging donors to reconsider their approach to solving nutrition challenges - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Over the past decade, reducing stunting has become a global development objective. A new A4NH study by IFPRI researchers challenges the assumptions underlying the attention to stunting and stresses the need to focus on more specific nutrition outcomes. Since its publication, the study has been extensively cited and donors have reported that the research has impacted on their decisions around which nutrition outcomes to focus on when funding and designing programs.